Language and bilingual cognition - Cook, Vivian, 1940-; Bassetti, Benedetta (New York, NY : Psychology Press, 2011)
Focusing on bilinguals, this text provides a state-of-the-art overview of the relationship between language and cognition.
Includes bibliographical references and indexes.
Keywords: Bilingualism -- Psychological aspects; Cognition; Psycholinguistics